ENHANCING CHILDREN FOREIGN LANGUAGE ACQUISITION THROUGH STORY TELLING: enhancing, children language acquisition, storytelling - Joesasono Oediarti (Universitas PGRI Adi Buana, 2010)
Children naturally enjoy stories. Children involved in education programs that utilize storytelling exhibit many positive behaviors related to increased literacy. Improved listening skills, vocabulary development and an increased ability to organize narrative thought are all behaviors exhibited by young children who have been exposed to a variety of stories on a consistent basis. Storytelling has emerged as a key cognitive skill in the process of intellectual development. Cognition that is enhanced in specific ways when children are exposed to a variety of stories can also be measured in qualitative ways. Storytelling is also an effective bridge to emergent literacy. Since we know that children are active participants in the acquisition of language, the interactive nature of show and tell or sharing time in the early grades is actually a recreation of a remembered experience. These tales are personal stories created by the children as a result of direct experience. The language patterns learned in these social contexts while children are interacting with adults and other children are constructed and reinforced as the teller becomes more proficient in relating the story. Reading stories aloud or listening and interacting with a storyteller are essentially a social experience. The development of vocabulary and syntactic complexity in oral language are more advanced in children who are frequently exposed to a variety of stories.